Use of the E-Raport Application in Improving Preschool Educators' Digital Literacy Competency - Eviani Masruroh Masrur (SEA-CECCEP, 2024)
It is hoped that the use of technology, especially the e-Report application, will open up opportunities to increase the understanding and application of digital literacy among ECCE educators. By focusing on the question of how implementing the e-Report application can enrich the digital literacy competencies of ECCE educators, this article explores various scientific literature to identify the benefits, challenges and implications of using this technology in the context of early childhood education. Through in-depth literature analysis, this article details the positive impacts that may result, such as increased efficiency, monitoring children's progress, and the integration of digital literacy in the teaching process. On the other hand, challenges related to policy, infrastructure and lecturer training are also considered to provide a balanced picture.